2002
DOI: 10.1136/adc.86.3.150
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the First Parent Health Visitor Scheme

Abstract: Aims: To assess outcomes in families who received the First Parent Health Visitor Scheme (FPHVS), in comparison with families who received conventional ("generic") health visiting. Methods: Retrospective data on 2113 families were collected during 1986-92 as part of National Health Service (NHS) service provision. Prospective data were collected during 1993-98 on 459 mothers and their children, with outcomes assessed at one year (93% follow up) and two years (80% follow up). Results: There were no differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 6 publications
(2 reference statements)
0
32
0
1
Order By: Relevance
“…The peer group is nevertheless clearly a crucial resource in helping many HVs formulate their difficult cases. Internationally, there have been many initiatives designed to help HVs provide support to families with difficulties in parent-child relationships (for example Barlow et al 2007;Collins & Reinke 1997;Emond et al 2002;Hewitt & Crawford 1988;McIntosh & Shute 2007;Olds 2002;Sanders et al 2003). There are however far fewer reports of how best to target the delivery of these interventions effectively towards those families who could gain most from them, and most of these have been based on simple demographics -for example Olds' seminal work on intensive home visitation was aimed at a target group of mothers who were in their teens, unmarried or living in deprived areas (Olds et al 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…The peer group is nevertheless clearly a crucial resource in helping many HVs formulate their difficult cases. Internationally, there have been many initiatives designed to help HVs provide support to families with difficulties in parent-child relationships (for example Barlow et al 2007;Collins & Reinke 1997;Emond et al 2002;Hewitt & Crawford 1988;McIntosh & Shute 2007;Olds 2002;Sanders et al 2003). There are however far fewer reports of how best to target the delivery of these interventions effectively towards those families who could gain most from them, and most of these have been based on simple demographics -for example Olds' seminal work on intensive home visitation was aimed at a target group of mothers who were in their teens, unmarried or living in deprived areas (Olds et al 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies 73,75,81,88 used clustered allocation. Thirteen studies [72][73][74][78][79][80]82,84,85,[88][89][90] [70][71][72]74,75,[77][78][79]81,[83][84][85]90 recruited socioeconomically disadvantaged participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Some authors reported results from the same study at different follow-up time points in separate papers and several authors reported results from the same study in more than one paper. Sixteen [70][71][72]74,[76][77][78]80,[82][83][84][85]87,89,90 (73%) included studies were RCTs, two 73,81 (9%) were non-RCTs, one 86 (5%) was a partially randomised study with two randomised intervention arms and one non-randomised control arm, two 75,88 (9%) were CBA studies and one 79 (5%) was a quasi-RCT. Four studies 73,75,81,88 used clustered allocation.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations